Optimizing the Role of Cadres in Increasing Knowledge in the Early Detection of Malnutrition Cases in Toddlers - Yani Maidelwita; Yulia Arifin (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Malnutrition is a condition in which the body does not get enough nutrition to maintain health. There were 59 cases of malnutrition in Padang City in 2019. By finding cases early, the handling of children under five will be done more quickly. The health cadres have an important role in relation to early detection of malnutrition. To determine how much the cadres knowledge increased after being given cadre training. This type of research is analytic research design with Quasy experiment pre-test and post-test. The sample in this study was 20 cadres who were taken by using of the sampling technique cluster random sampling. the data obtained that there is no significant difference in cadres knowledge about PHBS with p value 0.317, and there is a significant difference in cadres knowledge about malnutrition with p value 0.001 and post nutrition with p value 0.008.